JÜRGEN BASEDOW ET AL. (Eds.), Economic Regulation and Competition - Nottage, Luke (Zeitschrift für Japanisches Recht, 2003)
“Economic Regulation and Competition: Regulation of Services inthe EU, Germany and Japan” Edited by J. BASEDOW / H. BAUM / K. J. HOPT / H. KANDA / T. KONO Kluwer Law International, The Hague et al., 2002, 331 + xi pages; ISBN 90 411 1968 X